Exploring the Relationship between G-Quadruplex Nucleic Acids and Plants: From Plant G-Quadruplex Function to Phytochemical G4 Ligands with Pharmaceutic Potential - Andrea P. Falanga; Monica Terracciano; Giorgia Oliviero; Giovanni N. Roviello; Nicola Borbone (MDPI AG, 2022)
G-quadruplex (G4) oligonucleotides are higher-order DNA and RNA secondary structures of enormous relevance due to their implication in several biological processes and pathological states in different organisms. Strategies aiming at modulating human G4 structures and their interrelated functions are first-line approaches in modern research aiming at finding new potential anticancer treatments or G4-based aptamers for various biomedical and biotechnological applications. Plants offer a cornucopia of phytocompounds that, in many cases, are effective in binding and modulating the thermal stability of G4s and, on the other hand, contain almost unexplored G4 motifs in their genome that could inspire new biotechnological strategies. Herein, we describe some G4 structures found in plants, summarizing the existing knowledge of their functions and biological role. Moreover, we review some of the most promising G4 ligands isolated from vegetal sources and report on the known relationships between such phytochemicals and G4-mediated biological processes that make them potential leads in the pharmaceutical sector.